2009
DOI: 10.1111/j.1469-8137.2009.02823.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of cytosolic glutamine synthetase in nitrogen assimilation and recycling

Abstract: Summary Glutamine synthetase assimilates ammonium into amino acids, thus it is a key enzyme for nitrogen metabolism. The cytosolic isoenzymes of glutamine synthetase assimilate ammonium derived from primary nitrogen uptake and from various internal nitrogen recycling pathways. In this way, cytosolic glutamine synthetase is crucial for the remobilization of protein‐derived nitrogen. Cytosolic glutamine synthetase is encoded by a small family of genes that are well conserved across plant species. Members of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
377
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(388 citation statements)
references
References 153 publications
(216 reference statements)
8
377
0
3
Order By: Relevance
“…Nitrate reduction transcripts were significantly down-regulated by the stress, but ammonium assimilation into amino acids was not affected. This underlines the importance of the GS/GOGAT not just in primary assimilation but also for protein and amino acid turnover in the metabolically active leaf (Bernard and Habash, 2009). The amino acid pool decreased under N deprivation and the major amino acids reacted in coordination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrate reduction transcripts were significantly down-regulated by the stress, but ammonium assimilation into amino acids was not affected. This underlines the importance of the GS/GOGAT not just in primary assimilation but also for protein and amino acid turnover in the metabolically active leaf (Bernard and Habash, 2009). The amino acid pool decreased under N deprivation and the major amino acids reacted in coordination.…”
Section: Resultsmentioning
confidence: 99%
“…Ammonium is not only produced by nitrate assimilation but also an intermediate in protein turnover and photorespiration, and its immediate reassimilation prevents loss of N to the environment. Activity of GS1 is therefore highly regulated and adapted to the specific organ, cell type, or environmental condition (Bernard and Habash, 2009). The increase of ammonium in leaves from plants with reduced GS1 transcription also indicated that reassimilation of ammonium is highly dependent on GS1 presence and might be critical under conditions with N limitation (Bernard and Habash, 2009).…”
Section: Effects Of Low N On N Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it can be said that there is a strong link between leaf N metabolism and photosynthesis (Novitskaya et al, 2002), due to the positive correlation of glutamine synthesis in the malate shuttle between the cytosol and stroma (Stitt et al, 2002). Gas exchange is very closely related to the GS/GOGAT cycle and oxoglutarate is required for both GOGAT operations and carbon metabolism (Noctor and Foyer, 1998;Britto and Kronzucker, 2002;Bernard et al, 2009). Hence, in situations where the GS/GOGAT cycle changes (e.g., in our study, when our samples were affected by addition of different nitrogen forms), carbon metabolism (photosynthesis) may also be affected.…”
Section: Numerous Effects Of Inorganic N On Various Cultivarsmentioning
confidence: 97%
“…GS1 is located in leaf cytosol and a non-photosynthetic portion of the cells while GS2 is found in the chloroplast of photosynthetic cells (Ishiyama et al 2004;Bernard and Habash 2009;Wang et al 2015). Up-regulation of GS1 and GS2 emancipates NH 4 ?…”
Section: Introductionmentioning
confidence: 99%